Corporate governance and CSR reporting: CSRI evidence from 26 listed Vietnamese banks (2014–2024) - Viet, Ha Nguyen; The, Vinh Phung; Minh, Hien Nguyen (Edelweiss Applied Science and Technology, 2026)
This study examines how financial and governance structures affect the degree of corporate social responsibility (CSR) disclosure made by 26 Vietnamese listed commercial banks between 2014 and 2024. The study uses content analysis from sustainability and annual reports to create a CSR disclosure index (CSRRRI) with seven criteria based on the surplus resources perspective, legitimization theory, and stakeholder theory. FEM, REM, and FGLS models were used to analyze the panel dataset of 286 observations; FGLS was selected to handle autocorrelation and heteroskedasticity. The findings demonstrate that the degree of CSR disclosure is positively and statistically significantly impacted by bank size (STA) and return on assets (ROA). Alternatively, net interest margin (NIM) and return on equity (ROE) are negatively impacted. The percentage of foreign members (FOROWN) and non-executive members (COMPNED), two governance variables, are not statistically significant. Overall, the primary factors influencing CSR transparency in the Vietnamese context are organizational size and financial capability, while the board of directors’ oversight function is still quite small. The policy ramifications highlight the necessity of strengthening the board of directors’ substantive role, standardizing reporting in accordance with international standards, and improving the ESG legal framework to promote transparency and the banking system’s sustainable growth.